One-magnon and exciton inelastic light scattering in the antiferromagnet CoF2 - Meloche, E.; Cottam, M.G.; Lockwood, D.J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
Experimental data are reported for the temperature and polarization dependence of the one-magnon Raman light scattering in the rutile-structure antiferromagnet CoF2 (Néel temperature TN = 38 K). The low-lying excitons are also investigated at low temperatures and comparisons made with results from earlier Raman, infrared, and neutron scattering work. A detailed analysis of the one-magnon Stokes and anti-Stokes Raman spectra is presented resulting in comprehensive data for the temperature variation up to TN of the one-magnon frequency, line width, and integrated intensity. A theory of the one-magnon scattering and other magnetic transitions is constructed based mainly on a spin S = 3/2 exchange model, extending a simpler effective S = 1/2 approach. The excitation energies and spectral intensities over a broad range of temperatures are obtained using a Green’s function equation of motion method that allows for a careful treatment of the single-ion anisotropy. Overall the S = 3/2 theory compares well with the experimental data.